2021
DOI: 10.1186/s13017-021-00356-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of functional loss in emergency surgery is possible with a simple frailty screening tool

Abstract: Background Senior adults fear postoperative loss of independence the most, and this might represent an additional burden for families and society. The number of geriatric patients admitted to the emergency room requiring an urgent surgical treatment is rising, and the presence of frailty is the main risk factor for postoperative morbidity and functional decline. Frailty assessment in the busy emergency setting is challenging. The aim of this study is to verify the effectiveness of a very simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Clinicians provided in-hospital rehabilitation, especially for elderly patients, presumably considering the impaired activities of daily living after surgery. 7 , 8 Although rehabilitation could have aided short-term early mobilization, the current analysis with adjustment for preoperative comorbidities and activities of daily living demonstrated that age older than 65 years was substantially associated with poor long-term functional prognosis. Notably, the hazard ratio increased rapidly compared with that for mortality.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Clinicians provided in-hospital rehabilitation, especially for elderly patients, presumably considering the impaired activities of daily living after surgery. 7 , 8 Although rehabilitation could have aided short-term early mobilization, the current analysis with adjustment for preoperative comorbidities and activities of daily living demonstrated that age older than 65 years was substantially associated with poor long-term functional prognosis. Notably, the hazard ratio increased rapidly compared with that for mortality.…”
Section: Discussionmentioning
confidence: 76%
“…Impaired activity of daily living following surgery also is a serious concern among the elderly. 7 , 8 The impaired activity would result in poor quality of life; moreover, if a patient becomes bedridden, the condition is accompanied by several complications, such as bedsores, deep venous thrombosis, pneumonia, and urinary tract infections, deteriorating the optimal allocation of medical resources. 9 12 Because poor functional capacity will have a negative impact on survival, maintenance of function and independence has become one of the major principles of cancer management in the elderly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In elderly patients, the mortality rate in emergency surgery is about 15-30% and could increase up to 60% with comorbidities [13]. The latest study found 30-day mortality of emergency surgery in the elderly [14]. This surgical outcome is multiple times worse than elective surgery including in terms of morbidity and mortality, especially for those with multiple comorbidities [6].…”
Section: Discussionmentioning
confidence: 99%
“…The type of surgical intervention was categorized as either major or intermediate-minor. We defined major surgery as surgical interventions such as bowel resection, Hartmann’s surgery, or surgery for diffuse peritonitis and intermediate-minor surgery as cholecystectomy (excluding diffuse peritonitis), appendicectomy, dissection of adhesions, stoma creation without resection, hernia repair, diagnostic LS or OS [ 29 ].…”
Section: Methodsmentioning
confidence: 99%